Ontologi (Hakikat Ilmu) - Harsing; Adang Hambali; Adun Rahman (Idarotuna: Jurnal Manajemen Pendidikan Islam, 2024)
This study is motivated by an attitude of curiosity about the nature of science or ontology, to see the direction and development of Islamic education so that it needs to be studied from the meaning of ontology, metaphysics, foundations of metaphysics, branches of metaphysics, sources of metaphysical truth and uses of metaphysics. This study uses qualitative methods with a library approach. research), which aims to explore the deep meaning of a phenomenon, reality, or existing facts. Furthermore, to approach the problem a qualitative approach was used. The analysis used was content analysis and used descriptive-analytical methods. Then the main sources in this research are scientists' reference books on the philosophy of science and of course other sources related to the topic of discussion. The results of this study can be concluded. First, ontology asks fundamental questions about what exists and how these entities relate to each other. Ontology also contributes to the development of scientific paradigms. Ontology invites us to reflect on the relationship between subjects and objects in research. Finally, an ontological understanding of the nature of science can facilitate interdisciplinary dialogue. Overall, the ontology of the nature of science provides an important philosophical foundation in understanding and developing knowledge. By examining the reality behind science, we can better appreciate the complexity and beauty of the human quest for knowledge and truth.